Intertidal History in Island Southeast Asia: Submerged Genealogy and the Legacy of Coastal Capture - Gaynor, Jennifer L. (Cornell University Press, 2016)
Intertidal History in Island Southeast Asiashows the vital part maritime Southeast Asians played in struggles against domination of the seventeenth-century spice trade by local and European rivals. Looking beyond the narrative of competing mercantile empires, it draws on European and Southeast Asian sources to illustrate Sama sea people's alliances and intermarriage with the sultanate of Makassar and the Bugis realm of Boné. Contrasting with later portrayals of the Sama as stateless pirates and sea gypsies, this history of shifting political and interethnic ties among the people of Sulawesi's littorals and its land-based realms, along with their shared interests on distant coasts, exemplifies how regional maritime dynamics interacted with social and political worlds above the high-water mark.